2004
DOI: 10.1085/jgp.200308996
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sodium Channel Function by Bilayer Elasticity

Abstract: Membrane proteins are regulated by the lipid bilayer composition. Specific lipid–protein interactions rarely are involved, which suggests that the regulation is due to changes in some general bilayer property (or properties). The hydrophobic coupling between a membrane-spanning protein and the surrounding bilayer means that protein conformational changes may be associated with a reversible, local bilayer deformation. Lipid bilayers are elastic bodies, and the energetic cost of the bilayer deformation contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
153
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(169 citation statements)
references
References 160 publications
(196 reference statements)
14
153
2
Order By: Relevance
“…This lipophilic compound might indirectly affect CFTR gating by influencing bilayer thickness or membrane stiffness, as reported for other compounds and ion channels by Andersen and co-workers (37)(38)(39). However, four results seem more consistent with a direct binding model: (i) the activation of CFTR channels by curcumin saturates at increasing concentrations (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…This lipophilic compound might indirectly affect CFTR gating by influencing bilayer thickness or membrane stiffness, as reported for other compounds and ion channels by Andersen and co-workers (37)(38)(39). However, four results seem more consistent with a direct binding model: (i) the activation of CFTR channels by curcumin saturates at increasing concentrations (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Although the molecular details underlying the changes in single-channel activity in response to cellular cholesterol level are not clear, manipulation of cellular cholesterol content may have affected the physicochemical properties of the plasma membrane surrounding the BK Ca channel, such as lateral stress and curvature, which could affect channel activity as has been reported for gramicidin and sodium channels (37). In fact, it has been reported that cholesterol content of plasma membrane correlates inversely with the BK Ca activity because of altered membrane fluidity that affects kinetic properties of the channels (38).…”
Section: Discussionmentioning
confidence: 99%
“…In the continuum theory of liquid crystal deformations a bilayer deformation induced by an inclusion is decomposed into three different modes, and the corresponding elastic parameters, in principle, should be transferable from measurements in protein-free lipid systems. However, a strict separation between the energetic contributions to G cont is problematic [50,51], and a change in bilayer lipid composition will always alter more than one of the elastic parameters [14]. Therefore such transferal is difficult.…”
Section: The Hydrophobic Coupling Mechanismmentioning
confidence: 99%
“…where the coefficients H B , H X and H C are determined by r 0 , d 0 , K a , and K c [14,51]. The bilayer disjoining force on the channel, F, (=d G cont /d2u 0 ) is given by [9]:…”
Section: Gramicidin Channels As a Model Systemmentioning
confidence: 99%
See 1 more Smart Citation